Independent Corporate Governance Organs Activities And Tax Avoidance Activities: Evidence From Indonesia - Oktavia Oktavia (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2020)
This study aims to examine the effect of independent corporate governance organs activities (i.e. the level of busyness and political connections of independent corporate governance organs) on tax avoidance activities. By using a sample of manufacturing companies and panel data analysis, this study finds evidence that: (i) The busyness level of independent directors and audit committee have a positive effect on tax avoidance activities. This indicates that the more positions or jobs hold by independent directors and audit committees, thus their duties to monitor the company may be neglected and in turn they are unable to detect that the company is engaged in aggressive tax avoidance; (ii) Political connections of independent directors and audit committees have a positive effect on tax avoidance activities. This suggests that independent directors and audit committees can take advantage from their political connections to make a politics lobby that can reduce the corporate tax burden.